76.6k views
4 votes
3x - 2y = -2
–5z - 7y=1

User DV Singh
by
5.6k points

1 Answer

2 votes

Answer:


\displaystyle [-(16)/(31), (7)/(31)]

Explanation:

{3x - 2y = −2

{–5x - 7y = 1

2⁄7[–5x - 7y = 1]

{3x - 2y = −2

{1 3⁄7x + 2y = −2⁄7 >> New Equation

____________


\displaystyle (4(3)/(7)x)/(4(3)/(7)) = (-2(2)/(7))/(4(3)/(7)) \\ \\


\displaystyle x = -(16)/(31)[Plug this back into both equations above to get the y-coordinate of 7⁄31];
\displaystyle (7)/(31) = y

I am joyous to assist you anytime.

User Subchap
by
5.9k points